(untitled) (Journal of Governance and Development (JGD), 2021)
This article investigates the link between fiscal decentralization and fiscal autonomy in service delivery particularly in urban Local Government Authorities in Tanzania. In the past two decades, Tanzania government adopted fiscal decentralization reforms as part of broad local government reform program. The reforms include the transfer of fiscal power to local governments to collect and spend their own revenues but also to enjoy discretionary intergovernmental transfers from central government. On the contrary, local government authorities particularly in urban areas have not achieved the intended goal of the reforms. Most of the LGAs lack adequate fiscal autonomy to address the growing demand of urban services and infrastructure. Although there is already substantial amount of research explaining fiscal decentralization in Tanzania, most of this literature focuses on the limited revenue base of local government and lack of effective intergovernmental transfers. Overall, there is very little which is known concerning institutional factors which play a role when it comes to decision making on the allocation of fiscal resources to local government. The objective of this paper was therefore two folds: first to identify the current state of fiscal decentralization in two LGAs selected for this research and second was to explore the institutional factors which determine the allocation of fiscal resources in the selected urban LGAs in Tanzania. In addressing this objective, the comparative case study design was adopted namely: Kinondoni Municipal Council in Dar es Salaam region and Tunduma Town Council in Songwe region in Tanzania. The sample of 60 respondents was drawn purposely from the two cases and the data from the sampled respondents were collected through the review of documents, in-depth interviews and focus group discussion with officials in the selected urban LGAs. The collected data were finally analyzed through contents analysis for documentary review and thematic analysis for the interviews and focus group discussion. The research findings show that the degree of fiscal autonomy has substantially deteriorated in the past six years due to excessive central government guidelines and directives which regulate expenditure and revenue generation by local government. This includes the conditions on the allocation of fiscal resources such as budget or the use of intergovernmental transfers from central government.